What is the best approach to treat acute migraine in children in the emergency department? - Ghirigato, Elena; Zupin, Luisa; Celsi, Fulvio; Capaci, Valeria; Amaddeo, Alessandro; Cozzi, Giorgio (Frontiers in Pediatrics, 2025)
Migraine is a prevalent condition in children and adolescents, often presenting with severe symptoms that prompt visits to the emergency department (ED). This study aim was to evaluate which is the best approach for treating acute severe migraine in a pediatric ED setting by reviewing randomized controlled trials (RCTs). A systematic literature search was performed and identified 169 articles, of which six met the inclusion criteria, focusing on pediatric patients treated in the ED. The studies reviewed involved various analgesic regimens, including non-steroidal anti-inflammatory drugs (NSAIDs) like ketorolac, anti-dopaminergic drugs like metoclopramide and prochlorperazine, and other treatments like opioids, propofol, and ropivacaine. Available randomized controlled studies are few and heterogeneous in term of drug employed, and do not allow us to directly compare the studies and to identify the best treatment in the emergency department setting. Dopamine antagonists, with or without ketorolac, seems to be the best approach for acute severe migraine in adolescents presenting to the ED.